The cytokine milieu of bullous pemphigoid: Current and novel therapeutic targets - Maglie, Roberto; Solimani, Farzan; Didona, Dario; Pipitò, Carlo; Antiga, Emiliano; Di Zenzo, Giovanni (Frontiers in Medicine, 2023)
Bullous pemphigoid (BP) is the most common autoimmune bullous disease, characterized by severe pruritus and skin blistering. The loss of tolerance against Collagen XVII, also referred to as BP180, is the main pathogenic event of BP, leading to production of IgG autoantibodies which mainly target the juxtamembranous extracellular non-collagenous 16th A (NC16A) domain of BP180. A complex inflammatory network is activated upon autoantibody binding to the basement membrane zone; this inflammatory loop involves the complement cascade and the release of several inflammatory cytokines, chemokines and proteases from keratinocytes, lymphocytes, mast cells and granulocytes. Collectively, these events disrupt the integrity of the dermal-epidermal junction, leading to subepidermal blistering. Recent advances have led to identify novel therapeutic targets for BP, whose management is mainly based on the long-term use of topical and systemic corticosteroids. As an example, targeting type-2 T-helper cell-associated cytokines, such as Interleukin-4 and interleukin-13 has shown meaningful clinical efficacy in case series and studies; targeting IL-17 and IL-23 has also been tried, owing to an important role of these cytokines in the chronic maintenance phase of BP. In this review article, we discuss the complex cytokine milieu that characterized BP inflammation, highlighting molecules, which are currently investigated as present and future therapeutic targets for this life-threatening disease.